Multiple hazards and population change in Japan’s Suzu City after the 2024 Noto Peninsula Earthquake - Shohei Nagata; Erick Mas; Yuriko Takeda; Tomoki Nakaya; Shunichi Koshimura (Progress in Disaster Science)
The earthquake that struck Japan’s Noto Peninsula on January 1, 2024, caused extensive damage, leading to the first major tsunami warning since the 2011 Tohoku earthquake. It remains unclear where people moved immediately after the earthquake and how earthquake-induced multiple hazards affected human mobility, reflecting evacuation movement. This study examines the human mobility change in Suzu City, severely damaged by strong ground shaking and multiple hazards, including tsunamis and liquefaction, from January 1 to January 3, 2024, using population estimates based on cell phone networks. Specifically, we unravel the detailed spatiotemporal changes in population distribution in the affected areas, reflecting evacuation from the tsunami and other multiple hazard factors. Our results reveal that immediately after the earthquake, people concentrated in inland areas, suggesting that the major tsunami warning facilitated the evacuation from the coast to inland areas. Furthermore, the sense of strong ground shaking and tsunami inundation risk may have triggered tsunami evacuation. A clear drop in population was delayed by one to two days after the earthquake in areas with a high liquefaction potential and landslide occurrence. This study’s outcomes contribute to a better understanding of human mobility during disasters, thereby aiding future disaster-management decisions.